Effect of incorporation of wheat bran, rice bran and banana peel powder on the mesostructure and physicochemical characteristics of biscuits - Ayoub, Wani Suhana; Zahoor, Insha; Dar, Aamir Hussain; Anjum, Nadira; Pandiselvam, R.; Farooq, Salma; Rusu, Alexandru Vasile; Rocha, João Miguel; Trif, Monica; Jeevarathinam, G. (Frontiers in Nutrition, 2022)
Various types of natural fibre-rich ingredients are added into bakery-based products to improve their fibre content for health promotional purposes. However, most of these products are frequently added with imported dietary fibre ingredients. The aim of this study was to develop bakery products incorporated with wheat bran, rice bran and banana peel powder and to evaluate the effects on physicochemical properties and sensory acceptability of these different biscuit samples. Wheat bran, rice bran and banana peel powder was used to substitute refined wheat flour in biscuit samples at different levels (0, 5, 10, 15, 20, 25, and 30%). The effect of wheat bran, rice bran and banana peel powder incorporation on proximate composition, physical characteristics, texture profile, color and sensory evaluation of biscuit samples were investigated. The moisture content of the product showed significantly (p≤0.01) decreasing trend while as protein showed increasing trend with increasing level of incorporation of wheat bran, rice bran and banana peel powder. Also there was a considerable effect on L*, a*, and b* values of biscuit samples. Among the physical parameters diameter and thickness decreases non-significantly (p≤0.01) with the addition of different fibres whereas spread ratio and weight increases. Sensory attributes showed a significantly (p≤0.01) increasing trend with an increase in the level of incorporation with different fibres. Based on sensory values biscuits prepared with 15% wheat bran, 15% rice bran and 10% banana peel powder were rated best. The biscuits were packed in HDPE boxes and were analyzed on different intervals viz. 0, 30 and 60th day. Results revealed that during storage there was an overall decrease in ash content, protein, fat, and colour of the biscuits. However there was a considerable increase in moisture content during storage.